Analysis of key trends in the development of innovative potential of Ukraine - Yakymenko, Oleksandr (Skhid, 2013)
The article made a systematic analysis of the identified trends and factors for innovation potential of enterprises in Ukraine. It is concluded that Ukraine currently unable to provide Leading technology and high-tech industries as its parameters innovation and technological development have long been outside the boundary interval. Throughout the period of existence of Ukraine as an independent state there was nonequivalent foreign economic exchange, intensified its dependence on many external factors, including a supplier of natural raw materials and labor to multinationals and developed countries to focus global intellectual potential